1987
DOI: 10.1002/ajim.4700110204
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to lead and blood pressure: A study in 105 workers

Abstract: A group of workers, occupationally exposed to lead and cadmium compounds (n = 53), was compared to a group of workers not exposed to these metals (n = 52). The average values of systolic, diastolic, and mean blood pressure were found to be higher in the exposed group (p less than 0.05). In contrast with the correlation between CdU and blood pressure, the correlation between PbB and systolic and mean blood pressure remained statistically significant after controlling for age and pulse rate (r = 0.22, p less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…However, the full texts of four more articles could not be found [41][42][43][44], and thus the articles in question were excluded (Figure 1). Finally, a total number of six works was included in the meta-analysis [45][46][47][48][49][50] (Table 1, Figure 1). In these six articles, the exposed workers, identified by means of working medical histories, were nickel-cadmium battery factory workers, farmers, those working with pigments and cadmium resins, workers employed in the disposal of cadmium, steel industry workers, and workers in factories producing plastic materials.…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the full texts of four more articles could not be found [41][42][43][44], and thus the articles in question were excluded (Figure 1). Finally, a total number of six works was included in the meta-analysis [45][46][47][48][49][50] (Table 1, Figure 1). In these six articles, the exposed workers, identified by means of working medical histories, were nickel-cadmium battery factory workers, farmers, those working with pigments and cadmium resins, workers employed in the disposal of cadmium, steel industry workers, and workers in factories producing plastic materials.…”
Section: Search Strategymentioning
confidence: 99%
“…A subject was considered hypertensive when his systolic arterial pressure was equal to or higher than 140 mmHg, or the diastolic arterial pressure was equal to or higher than 90 mmHg, according to the latest guidelines established by the World Health Organization (WHO) [50]. Cadmiemia, which was analyzed in four studies, and obtained by the use of atomic absorption spectrometry with graphite furnace [45][46][47]49] was expressed in μg/l. However, cadmiuria was expressed in μg/g of creatinine in three studies: by the use of atomic absorption spectroscopy [46], atomic absorption spectrometry using carbon rods [48] or the modified method of Pruszowska [49].…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…At high exposure levels, lead causes encephalopathy (6,7), kidney damage (8,9), anemia (10), and toxicity to the reproductive system (11,12). Lead exposure may also induce hypertension in some individuals (13,14). Even at lower doses, lead produces alterations in cognitive development in children (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Studies on animals and human subjects have suggested that urban pollutants may alter blood pressure (BP) values; these agents are cadmium [1][2][3][4][5] , lead [6][7][8][9][10][11][12] benzene, toluene and xylene 13,14) . Besides these, physical agents such as noise [15][16][17][18][19] and psycho-social stressors [20][21][22][23] could alter BP values.…”
mentioning
confidence: 99%